Hospital costs associated with nosocomial infections in a pediatric intensive care unit - Áurea Morillo-García; Josefa M. Aldana-Espinal; Antonio Olry de Labry-Lima; Raquel Valencia-Martín; Reyes López-Márquez; Mercedes Loscertales-Abril; Manuel Conde-Herrera (Elsevier, 2015)
Objective: To estimate the additional cost attributable to nosocomial infection (NI) in a pediatric intensive care unit (PICU) and related factors. Methods: A prospective cohort study was conducted in all children admitted to the PICU of a tertiary-care pediatric hospital between 2008 and 2009. Descriptive and bivariate analyses were conducted of total direct costs due to PICU stay and medical procedures in patients with and without NI. A log-linear regression model was performed to determine the factors associated with higher total cost. Results: A total of 443 patients were studied and the prevalence of NI was 11.3%. The difference in the median total cost was €30,791.4 per patient between groups with and without NI. The median cost of PICU length of stay in patients with NI was almost eight times higher than the median cost of patients without NI. In patients with NI, the highest costs related to medical procedures were associated with antibiotics, enteral and parenteral feeding, and imaging tests. In the multivariate model, the factors associated with higher cost were infection, the performance of cardiovascular surgery, urgent admission, a higher pediatric risk mortality score, and the presence of immunosuppression. By contrast, older children and those with surgical admission generated lower cost. Conclusions: NI was associated with an increase in total cost, which implies that the prevention of these infections through specific interventions could be cost-effective and would help to increase the safety of healthcare systems.